A comparative evaluation of Indole-3-Butyric Acid and plant extracts as potential rooting enhancers in cuttings of Vitex diversifolia and Cordia milleneii - Shidiki, Abubakar Ali; Ambebe, Titus Fondo; Mendi, Anjah Grace (International Journal of Forest, Animal and Fisheries Research, 2019)
This study tested the effect of a synthetic phytohormone and plant extracts on rooting of cuttings. Treatments comprised of two tree species (Cordia mellineii and Vitex diversifolia) and five pre-planting rooting treatments (untreated control, Indole-3-Butyric Acid (IBA), aloe vera gel (AV), coconut water (CW), and AV+CW in the ratio 1:1 v/v) laid out in split-plot. Data were collected four months after the application of treatments. There was neither rooting of Cordia mellineii cuttings in any of the treatments nor Vitex diversifolia cuttings in the control. Rooting percentage of Vitex diversifolia was highest in AV+CW and lowest in the AV treatment which did not show a significant difference with the control. In contrast, values of number of primary roots were highest in AV. Number of secondary roots, root system length and root fresh weight were significantly reduced by IBA. Root diameter was unresponsive to rooting enhancing treatments. The results suggest that biostimulators are essential for rooting of Vitex diversifolia cuttings. While IBA, AV, and CW may have a comparable influence on root initiation, the two plant extracts have the tendency to exhibit a stronger effect when in combination. In addition, IBA may be less beneficial for root growth than AV and CW.